Do Learning Benefits Accrue Equally Over Successive Fundraising Attempts? Strategic Change and the Moderating Role of Experience. (20th October 2021) - Sewaid, Ahmed; Garcia‐Cestona, Miguel; Silaghi, Florina
Abstract: In the management literature, the role of learning from experience and its effect on performance has been highlighted. However, little is known about the effects of strategic change on performance due to aspects pertaining to the mobility of learning. Building on different learning theories, we theorize about the effect of strategic change on performance when: (i) strategic change does not require the mobilizing of resources; (ii) strategic change does not involve exposure to a new set of stakeholders; and (iii) time commitment to previous strategies is low. We confront our contentions with data on serial campaign launchers in crowdfunding. The data indicates that changing industry adversely affects fundraising performance due to the specificity of a portion of the accrued learning. This adverse effect is mitigated by venture launching experience and exacerbated following failure. Implications for practitioners and scholars are discussed.